Three-dimensional electron microscopy of macromolecular assemblies - Frank, J. (Joachim), 1940- (Academic Press, 1996)
Three-Dimensional Electron Microscopy of Macromolecular Assemblies is the first systematic introduction to single-particle methods of reconstruction. It covers correlation alignment, classification, 3D reconstruction, restoration, and interpretation of the resulting 3D images in macromolecular assemblies. It will be an indispensable resource for newcomers to the field and for all using or adopting these methods. Key Features * Presents methods that offer an alternative to crystallographic techniques for molecules that cannot be crystallized * Describes methods that have been instrumental in exploring the three-dimensional structure of * the nuclear pore complex * the calcium release channel; * the ribosome * chaperonins.